(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cardiac ischemia initiates a complex sequence of biochemical and structural disturbances that progressively impair the integrity and function of cardiomyocytes. Prolonged oxygen and nutrient deprivation lead to energy depletion, ionic imbalance, mitochondrial dysfunction, and disruption of cellular membranes. These events trigger cytoplasmic swelling, loss of myofibrillar organization, calcium overload, activation of proteolytic enzymes, and ultimately irreversible necrosis. Histologically, ischemic cardiomyocytes demonstrate sarcolemmal rupture, nuclear pyknosis, eosinophilic cytoplasm, loss of cross-striations, and inflammatory cell infiltration. A detailed understanding of these degradation processes is essential for accurate diagnosis, staging of myocardial injury, and developing targeted interventions aimed at minimizing tissue damage and improving clinical outcomes in ischemic heart disease.